Pharmacological and Non-Pharmacological Intervention to Prevent Preeclampsia: A Systematic Literature Review - Fatimatasari - Fatimatasari; Fatimah Fatimah; Angela C.B Trude; Herlin Herlin Fitriana Kurniawati; Rosmita Nuzuliana (Alma Ata University Press, 2020)
Preeclampsia is a disorder of pregnancy that increases risk for long-term health consequences for both mother and child, and if left untreated is one of the main causes of maternal and fetal mortality. However, delivery of the placenta is the only cure, making prevention options for this condition needed but little consensus exist on their effectiveness. Thus, we conducted a systematic literature review on the effectiveness of pharmacological interventions and dietary supplementations to prevent preeclampsia. We used MEDLINE and ProQuest to conduct a systematic search for peer-review publications on prevention of preeclampsia. We selected studies conducted in human and published in English from 2010 through 2020 on: i) types of interventions; ii) quality of studies and limitations. We selected 22 articles to be reviewed. Three types of pharmacological interventions and eight types of dietary supplementations were identified. Nitric Oxide-donors with Isosorbide Mononitrate (IMN), and aspirin have been shown to be effective, while selenium, calcium, vitamin D, DHA-rich fish oil-concentrate, copper, phytonutrient, Nitric Oxide-donors with Penthaerythrityl Tetranitrate (PETN), folic acid, vitamins C and E and magnesium have not been proved effective to prevent preeclampsia. Although all studies presented good quality of evidence, they had several limitations, the most common limitations are lack of initial therapy, lack of dosage, and inadequate sample size to detect small effect. Despite the growing evidence of treatments to prevent preeclampsia, their effect is not large. More research is needed in the field before prevention treatments are prescribed in clinical settings.